Impact of money supply in different states of inflation and economic growth in South Africa - Eugene Msizi Buthelezi (Economies, 2023)
This paper investigates the impact of the money supply in different states of inflation and economic growth in South Africa from 1990 to 2021. The term 'states' defines periods of low and high rates of economic variables of interest. Markov-switching dynamic regression (MSDRM) and time-varying parameter structural vector autoregression (TVP-VAR) are used in this paper. The contribution of this paper is not only based on the long run but also on the examination of the impact of the money supply in different states of inflation and economic growth. Moreover, the use of shock accounts for time-varying elasticity. It is found that there is a 0.70% decrease in the gross domestic product for a 1% increase in money supply in state 1, while in state 2, the money supply was insignificant. The money supply had a negative and a positive impact on inflation in states 1 and 2, with rates of 0.05% and 0.35% in the respective states. The money supply had a high multiplier effect on gross domestic product and inflation. More than 5 years were spent in each state for both gross domestic product and inflation, while the transition probability of moving and returning to each state is significant. The trade-off of using the money supply for economic growth and inflation is evident in South Africa. It is recommended that the state of the economy be considered when using the money supply in an effort to stimulate economic growth or stabilise inflation.
Keywords: E51; E52; F43; 330; broad money; economic growth; Markov-switching dynamic regression (MSDRM); money supply; time-varying parameter structural vector autoregression (TVP-VAR)